Equal pay - CAWU leaflet, c. 1960 (1960)
1960 1960-2000 "Equal pay - CAWU leaflet, c. 1960" [EP0154], 1960 Leaflet from the Clerical and Administrative Workers' Union for women working in the engineering industry. The Union had submitted a claim for the introduction of equal pay over 5 years which the Engineering and Allied Employers National Federation had rejected.